A comprehensive in silico analysis of structural and functional impacts of natural nonsynonymous SNPs in the ALDH2_HUMAN gene - Mehr Ali Mahmood Janlou (Egyptian Journal of Medical Human Genetics)
Abstract Background nsSNPs result in amino acid substitutions in coding regions that contribute significantly to the structural diversity of proteins in human populations and can affect protein function by altering solubility or stability. Mitochondrial aldehyde dehydrogenase 2 (ALDH2) is a key enzyme involved in the metabolism of acetaldehyde to acetate through a coenzyme-dependent mechanism. Acetaldehyde exhibits a toxic effect, highlighting the necessity of ALDH2’s proper functioning to protect against diseases associated with aldehyde toxicity. ALDH2 has three natural variants: E487K, E479K, and E320V. Consequently, it seems necessary to investigate the underlying molecular basis of the effect of each of these mutations on enzyme structure and function. Results Employing molecular docking and scoring functions of NAD+ at the prosthetic site of ALDH2 indicate that only E487K significantly reduces binding affinity and has a higher inhibition constant. Furthermore, performing microsecond-timescale molecular dynamics simulations revealed that only the E487K mutation elevated the conformational instability and induced less compactness of the ALDH2. To compare the results, four distinct SNP predictors were employed. The outcomes generated by these tools were noteworthy and corroborated the results obtained from the molecular docking and dynamics simulations, indicating that only the E487K variant was identified as a deleterious mutation. Conclusions This study revealed that among three natural variants of ALDH2, only the E487K significantly reduces the interaction between NAD+ and ALDH2 due to structural instability in the enzyme, disrupting critical interactions with Cys302 and Glu268 required for enzyme activity. The exploration of the dynamic behavior of the dominant negative mutant in this investigation will contribute essential knowledge toward the potential restoration of its function.